Efektivitas Slow Stroke Back Massage (SSBM) Terhadap Nyeri Akut Pasien Post Sectio Caesarea di Ruang HCU Maternal RSUD Dr. Margono Soekarjo Purwokerto - Konitasari, Rizky Rofiana; Wahyu Ningrum, Ema (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2025)
Sectio Caesarea (SC) delivery has side effects such as severe pain in the postoperative wound. Pain is an unpleasant symptom experienced by post sectio caesarea patients. Pain in post sectio caesarea can be treated with various alternatives, both pharmacological and non-pharmacological. Pharmacologically, it can be treated with analgesic drugs. One natural method that is considered effective in reducing pain is Slow Stroke Back Massage therapy. This case study aims to describe the application of Slow Stroke Back Massage therapy in Post Sectio Caesarea Patients With Acute Pain at Dr Margono Soekarjo Purwokerto Hospital. Case studies conducted by observation for 3x meetings and interventions providing Slow Stroke Back Massage therapy for 3 days on 16-18 January 2025. The results of the case study of the application of Slow Stroke Back Massage therapy on the first day the patient was still in pain and showed a decrease in the pain scale on the second day. On the first day, the patient's pain intensity before being given Slow Stroke Back Massage therapy with a pain scale of 7 (severe pain), on the second day there was a decrease in pain scale after giving Slow Stroke Back Massage therapy to scale 5 (moderate pain) and on the third day there was a significant decrease in pain scale after giving Slow Stroke Back Massage therapy to scale 3 (mild pain). Giving Slow Stroke Back Massage therapy to Post Sectio Caesarea Patients With Acute Pain at Dr. Margono Soekarjo Purwokerto Hospital is effective in reducing pain applied for 3x24 hours showing significant results from a pain scale of 7 (severe pain) to a pain scale of 3 (mild pain).